Employability of Postgraduate Scholars in Rajasthan - Shubham Mishra, K.L. Dangi, G.S. Bangarv and Baldeo Singh (Indian Journal of Extension Education, 2023)
The study of the employability of postgraduate scholars was conducted in the state of Rajasthan by selectingthree agriculture universities MPUAT (Udaipur), SKNAU (Jobner), SKRAU (Bikaner) purposively fromamong three universities 90 respondents were selected randomly. The basic information regarding thepostgraduate research scholars was collected from the P.G. & Ph.D scholars. Thirteen components wereselected as indicators of overall employability of postgraduate scholars. The overall distribution ofemployability shows that a great majority of the postgraduate scholars (72.22 per cent) studying inAgricultural Universities in Rajasthan expressed medium level of overall employability. Separatelyemployability of the postgraduate scholars (70 per cent) studying in MPUAT (RCA) Udaipur was high.About 63.33 per cent of the scholars studying in SKNAU (Jobner) and 90 per cent of the postgraduatescholars studying in SKRAU (Bikaner) were from medium level of employability respectively.